Waste Management Education with Composting Takakura Home Method - Isradi, Muhammad; Andraiko, Heru; Yusman Firdaus, Hendy; Hasdian, Elhazri; Sudrajat, Kukuh Mahi; Abdila, Syafiadi Rizki; Syafwandi (Al-Qalam Institute, 2023)
One of the environmental problems that affect environmental and human health is waste generated from various human activities. Managing and sorting waste based on its type will make it easier to choose the next processing step, which will help reduce it. Sekolah Alam Robbani is one of the educational units with MI level in Jatisampurna Bekasi which has quite a lot of students. This school with the concept of nature in its activities is under the Ministry of Religious Affairs. The purpose of this community service is to promote environmental awareness, waste management education and composting of food waste and management. The method used is by providing material and direct practice of Tatakura Home Method Compost processing procedures. Evaluation and results of activities by dividing students into small groups and this is effective, students are able to prepare the ingredients and what steps in making this compost and are able to practice directly how to make and process Tatakura Home Method compost.